Knockdown of Circ_SLC39A8 protects against the progression of osteoarthritis by regulating miR-591/IRAK3 axis - Jizhe Yu; Yushuang Qin; Naxin Zhou (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The dysregulation of circular RNAs (circRNAs) has been identified in various human diseases, including osteoarthritis (OA). The purpose of this study was to identify the role and mechanism of circ_SLC39A8 in regulating the progression of OA. Methods The expression levels of circ_SLC39A8, miR-591, and its potential target gene, interleukin-1-receptor-associated kinase 3 (IRAK3), were identified by quantitative real-time polymerase chain reaction (qRT-PCR). Cell viability and apoptosis were determined by Cell Counting Kit-8 (CCK-8) assay and flow cytometry, respectively. The relationship between miR-591 and circ_SLC39A8 or IRAK3 was predicted by bioinformatics tools and verified by dual-luciferase reporter. Results Circ_SLC39A8 and IRAK3 were upregulated and miR-591 was downregulated in OA cartilage tissues. Knockdown of circ_SLC39A8 inhibited apoptosis and inflammation in OA chondrocytes, while these effects were reversed by downregulating miR-591. Promotion cell viability effects of miR-591 were partially reversed by IRAK3 overexpression. Conclusion Our findings indicated that knockdown of circ_SLC39A8 delayed the progression of OA via modulating the miR-591-IRAK3 axis, providing new insight into the molecular mechanisms of OA pathogenesis.